The association between stress hyperglycemia ratio with mortality in critically ill patients with acute heart failure - Ge, Tingai; Hu, Jingjing; Zhou, Yidan (Frontiers in Cardiovascular Medicine, 2024)
BackgroundIt's recognized that stress hyperglycemia ratio (SHR) is considered a significant indicator of poor prognosis in many diseases. However, its role in critically ill patients with acute heart failure (acute HF) remains underexplored.MethodsWe conducted a retrospective cohort study on patients with acute HF included in the Medical Information Mart for Intensive Care IV (MIMIC-IV) version 2.2 database. A restricted cubic spline (RCS) regression analysis was used to explore the relationship between SHR and the risk of all-cause mortality in these patients. Subsequently, a Cox regression model was used to evaluate the relationship between SHR and mortality in acute HF patients.ResultsA total of 1,644 acute HF patients were included in the study and divided into two groups: the low SHR group (SHR < 1.06, N = 823) and the high SHR group (SHR ≥ 1.06, N = 821). In our study, the 30-day, 90-day, 180-day, and 365-day mortality rates for acute HF were 7.0%, 12%, 15%, and 19%, respectively, with higher mortality rates observed in the high SHR group compared to the low SHR group. SHR levels showed a linear relationship with all-cause mortality. Furthermore, SHR as a continuous variable shows a significant positive correlation with 30-day (HR = 2.31, 95% CI: 1.58–3.39), 90-day (HR = 1.81, 95% CI: 1.31–2.52), 180-day (HR = 1.57, 95% CI: 1.16–2.12), and 365-day (HR = 1.41, 95% CI: 1.07–1.85) all-cause mortality. After categorization, high SHR remains associated with increased 30-day (HR = 2.4, 95% CI: 1.59–3.61), 90-day (HR = 1.76, 95% CI: 1.31–2.36), 180-day (HR = 1.51, 95% CI: 1.16–1.95), and 365-day (HR = 1.38, 95% CI: 1.09–1.73) all-cause mortality.ConclusionOur findings indicate that high SHR is an independent predictor of poor short- and long-term prognosis in acute HF patients. Understanding the impact of SHR on mortality in acute HF is crucial as it can assist clinicians in identifying high-risk patients and adjusting treatment strategies accordingly.